High-density lipoprotein nanoparticles spontaneously target to damaged renal tubules and alleviate renal fibrosis by remodeling the fibrotic niches - Shanshan He; Xiaoyang Li; Yuanyuan He; Ling Guo; Yunzhou Dong; Leilei Wang; Lan Yang; Lin Li; Shiyun Huang; Jiali Fu; Qing Lin; Zhirong Zhang; et al. (Nature Communications)
Abstract Chronic kidney disease (CKD) ultimately causes renal fibrosis and end-stage renal disease, thus seriously threatens human health. However, current medications for CKD and fibrosis are inefficient, which is often due to poor targeting capability to renal tubule. In this study, we discover that biomimetic high-density lipoprotein (bHDL) lipid nanoparticles possess excellent targeting ability to injured tubular epithelial cells by kidney injury molecule-1(KIM-1) mediated internalization. Thus, we co-load anti-inflammatory drug triptolide (TP) and anti-fibrotic drug nintedanib (BIBF) on bHDL nanoparticles to treat CKD. Based on the targeted delivery and mutual enhancement of the efficacy of co-delivered drugs, the bHDL-based system effectively reduces kidney injury and alleviates renal fibrosis in different CKD mouse models. The mechanistic study shows that BIBF and TP synergistically remodel the fibrotic niches by decreasing inflammatory cytokines, limiting immune cell infiltration and inhibiting the activation of myofibroblasts. The bHDL vehicle also possesses high manufacturability, good safety and adequately reduces the toxicity of TP. Thus, this system is promising for the treatment of CKD and bHDL has good potential for delivering agents to damaged renal tubular epithelial cells.